Isolation and identification of a native microbial consortium for the coffee pulp degradation above 2000 masl. - Arteaga-Cuba, M.N. (2021)
Pulp and mucilage constitute the most abundant by-products of the processing of coffee and inadequate handling produces high-rates of pollution. Considering that in nature there is a large variety of cellulolytic microorganisms which can intervene in the degradation of coffee pulp, the inclusion of a native microbial cellulolytic consortium was assessed. The sample for isolation consisted of coffee pulp and soil from a humid forest at more than 2,000 masl. Nutrient agar was used as a means of isolation for bacteria, and malt agar for fungi, supplemented with 50% soil extract and 1% carboxylmethylb-cellulose. This achieved the isolation of 118 strains of bacteria and 114 of fungi. Cellulolytic activity was established using the filter paper test, assessing and selecting only those that presented higher glucose production, among them 12 strains of fungi and 11 strains of bacteria. To obtain the microbial con-sortium, randomized blends were performed for both fungi and bacteria, again assessing the production of glucose. The bacterial consortium was made up of Ochrobactrum pseudo grignonense, Paenibacillus lauruscon and Bacillus xiamenensis and the fungal consortium by Fusarium sp., Penicillum sp., Cylindrocarpon sp. The optimal treatment achieved a complete degradation of the pulp in 28 days, that would contribute to the recovery and conservation of the coffee ecosystem. The main interpretation was that a wet environment at more than 2,000 masl is still suitable for coffee composting but different bacterial and fungi consortia were found to support other recent work done with one type of consortium.